Alat ukur untuk menilai kemampuan fungsional pasien dengan osteoartritis lutut: tinjauan pustaka - Sayu Aryantari Putri Thanaya; Stanisela Agatha; Luh Putu Ratna Sundari (Intisari Sains Medis, 2021)
Background: Osteoarthritis is a common disease that has become one of the main causes of disability and is ranked fourth as a contributing factor of disability. In Indonesia, many healthcare professionals, including physiotherapists, treat patients with various stages of osteoarthritis. Physiotherapists have a crucial role in improving the functional ability of patients with knee osteoarthritis. However, many of them do not use appropriate outcome measures to document patients’ improvements.Objective: This literature review aimed to summarize the available outcome measures that can be used to measure the functional ability of patients with knee osteoarthritis, in order to increase the awareness and knowledge of healthcare professionals, particularly physiotherapists, regarding the use of available outcome measures.Methods: The method used was literature review. Literature search was conducted in PubMed and Google Scholar databases using the main keywords: “outcome measure”, “scale”, “questionnaire”, “knee”, “osteoarthritis”, “functional ability”, “validity” and “reliability”.Result: This review identified 7 outcome measures in the form of questionnaires that can be used to measure the functional ability of patients with knee osteoarthritis. The most commonly used measure is the Western Ontario and McMaster University osteoarthritis index, which has been translated and validated in various languages. All measuring instruments were established in developed countries, except for the Ibadan Knee Osteoarthritis Outcome Measure. None of the 7 outcome measures have been translated and validated into Indonesian.Conclusion: This literature review has summarized measuring tools that can be used to measure the functional ability of patients with knee osteoarthritis. To date, no tools have been translated and validated into Indonesian. In the future, it is hoped that further research can be conducted in the form of cross-cultural adaptations studies on the validity and reliability of these outcome measures into Indonesian to support the effectiveness of using these measures to assess the functional ability of patients with knee osteoarthritis.  Latar belakang: Osteoartritis merupakan penyakit umum yang menjadi salah satu penyebab utama kecacatandan menempati urutan keempat untuk faktor penyebab kecacatan. Di Indonesia, banyak tenaga kesehatan, termasuk fisioterapis, yang merawat pasien dengan bebagai stadium osteoartritis. Fisioterapis sangat berperan dalam meningkatkan aspek fungsional pasien dengan osteoartritis lutut. Namun, banyak yang masih belum menggunakan alat ukur yang sesuai untuk mendokumentasikan kemajuan pasien.Tujuan: Tujuan tinjauan pustaka ini adalah untuk merangkum alat ukur yang dapat digunakan untuk mengukur kemampuan fungsional pasien dengan osteoartritis lutut, guna meningkatkan pengetahuan dan kesadaran tenaga kesehatan, terutama fisioterapis, dalam penggunaan alat ukur yang tersedia.Metode: Metode penelitian yang digunakan adalah tinjauan pustaka. Penelusuran artikel dilakukan pada database PubMed dan Google Scholar dengan kata kunci utama: “outcome measure”, “scale”, “questionnaire”, “knee”, “osteoarthritis”, “validity” dan “reliability”. Hasil: Tinjauan pustaka ini menemukan 7 alat ukur dalam bentuk kuisioner yang dapat digunakan untuk mengukur kemampuan fungsional pasien dengan osteoartritis lutut. Alat ukur yang paling sering digunakan adalah Western Ontario and McMaster University osteoarthritis index, yang sudah diterjemahkan dan divalidasi ke dalam berbagai bahasa. Semua instrumen pengukuran dibuat oleh negara maju, kecuali Ibadan Knee Osteoarthritis Outcome Measure. Dari 7 kuisioner, belum ada yang diterjemahkan dan divalidasi ke dalam Bahasa Indonesia.Kesimpulan: Tinjauan pustaka ini telah merangkum alat ukur yang dapat digunakan untuk mengukur kemampuan fungsional pasien dengan osteoartritis lutut. Sampai saat ini, belum ada kuisioner yang sudah diterjemahkan dan divalidasi ke dalam bahasa Indonesia. Diharapkan adanya pengembangan penelitian berupa studi adaptasi lintas budaya terhadap validitas dan realibilitas kuisioner lainnya ke dalam bahasa Indonesia untuk menunjang efektivitas penggunaan alat ukur dalam menilai kemampuan fungsional pasien dengan osteoartritis lutut.